F14 Early and progressive liver steatosis in kids carrying >80 CAG mutations and proven paediatric Huntington disease. (12th September 2022) - Squitieri, Ferdinando; Monti, Lidia; Graziola, Federica; Colafati, Giovanna Stefania; Sabatini, Umberto
Abstract : Background: When the CAG mutation in HTT gene is highly expanded >80 repeats, paediatric Huntington disease (PHD) may manifest since the first years of life. PHD mutations are highly mosaic and contribute to an atypical, disabling and shorten life span phenotype, compared to adulthood HD (AHD). Aim: Exploration of additional affected body districts which may explain the PHD severity and potentially provide rationale for seeking new clinical and biological markers. Methods: Our PHD cohort of kids with mutation >80 CAG repeats underwent a preliminary general ultrasound followed by Acoustic Radiation Force Impulse (ARFI) imaging which is a non invasive, elasto-graphic based ultrasound modality to investigate liver stiffness using shear wave velocity (SWV). Results: All PHD kids (2F, CAG: 84-114, age at onset: 2-5 years) showed increased liver volume and steatosis. The youngest 5-years old patient with 114 repeats showed initial steatosis since the first assay meaning that the mutation length may have played a critical role. All the kids did not manifest risk factors for fatty liver. A cohort of 600 Enroll-HD adult patients did show liver abnormalities in 8 cases, most of them with advanced HD and/or with comorbid conditions and pharmacological treatments that may potentially explain a hepatic disease. Conclusion: We eager to explore biological changes that may contribute to the early, CAG mutation and HD disease-progression dependent, liver steatosis. PHD shows a life span shorter than AHD even because large sized mutations cause a severe systemic extension of the pathology to periphery.